Characterization of Microparticles Extracted from Wasabi (Wasabia japonica) as a Natural Food Preservative for Fresh Chicken Meat - Mahmudah, Daimatul; As'idah, Fizriyatul; Rukmini, Rukmini; Maghfiroh, Khoirin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Chicken meat is a food ingredient vulnerable to contamination, requiring effective treatment to extend its shelf life and maintain quality. Wasabi (Wasabia japonica), a typical Japanese plant, contains an allyl isothiocyanate compound with antibacterial properties, making it a potential natural preservative. Therefore, this study aimed to develop microparticles of wasabi extract for application as a preservative for fresh chicken meat. In the process, microparticles were produced using the dry spray method, with maltodextrin as a coating material. The formulations tested were 0% (F0), 1% (F1), 2% (F2), and 3% wasabi extracts (F3), combined with 100 grams of maltodextrin and 1000 mL of distilled water. The produced microparticles were subjected to characterization to determine particle size, solubility test, particle morphology, crystal structure, and functional group identification. Subsequently, inhibition zone tests and total plate count were conducted to assess the effectiveness of the particles as a natural food preservative. The results showed that the F3 treatment had the widest inhibition zone (7.1 mm). Immersing chicken meat in the extract solution reduced the bacterial colony count from 16.8x106 CFU/gram to 12.5x106 CFU/gram over 6 days of storage. Therefore, F3 was the best formulation based on microbiological test results. This signified the potential of wasabi extract microparticles as a natural food preservative.